The effect of company size, institutional ownership, profitability and leverage on dividends payout ratio - Widodo, Febry Pamungkas Tri; Praptapa, Agung; Suparlinah, Irianing; Setyorini, Christina Tri (Journal of Contemporary Accounting, 2021)
The implication of this research is that company managers are expected to make dividend payout ratio decisions by looking at the factors that influence it, this is hoped that the company can avoid agency problems that can cause agency costs in the company, for corporate investors it is expected to be used as reference material for investing in the company by looking at the factors that affect the dividend payout ratio before investing, this study is expected to provide information about the factors that can affect the dividend payout ratio in the financial sector companies and is expected to be used as a reference for further research in the field of dividend payout ratios, further researchers can add other variables to find out other variables that affect the dividend payout ratio. This study is a study that uses secondary data and this study aims to determine the effect of company size, institutional ownership, leverage, and profitability on dividend payout ratio. The population in this study were financial sector companies on the Indonesian stock exchange in the period 2016-2018. The sample in this study were 16 companies in a 3year period. The sampling technique used was purposive sampling and the data analysis used was multiple linear regression analysis. The results of this study indicate that institutional ownership and profitability have a significant positive effect on the dividend payout ratio. Meanwhile, the variable company size and leverage does not have a significant effect on the dividend payout ratio.